2014
DOI: 10.1590/s0102-053620140000400011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potato genotypes for resistance to Diabrotica speciosa

Abstract: The potato a crop is attacked by many pests, among which the Diabrotica speciosa (Coleoptera: Chrysomelidae) is considered the main one. Because of chemical control failures associated with the requirements of integrated potato production (IPP) requiring sustainable measures, aimed to characterize advanced clones breeding program of Embrapa for resistance to insect infestation in artificial conditions. Tests were performed in a greenhouse without choice of plants and tubers of four clones of Embrapa (C2337-06-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…From knowledge, the development, survival, rhythm of oviposition, fecundity and fertility of D. speciosa are influenced negatively by maize varieties, possibly the existence of any morphological barriers in the roots of these plants is already possible the correlation with the resistance of plants to the larval attack of the species (Costa et al, 2018). Another study showed that adults of D. speciosa when fed with bean leaves, carrot and honey (10%) has higher fecundity and net reproductive rate compared to those adults that fed only of bean leaves (Teodoro et al, 2014). More, Garcia et al (2014) argued that the corn when intercropped with other plants, such as potatoes, soybeans and beans, can affect the spread of adults of D. speciosa in the field, functioning as a natural barrier to this pest, providing population reduction through the insertion corn lines near the starting point of invasion of the pest in the field, acting as the control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…From knowledge, the development, survival, rhythm of oviposition, fecundity and fertility of D. speciosa are influenced negatively by maize varieties, possibly the existence of any morphological barriers in the roots of these plants is already possible the correlation with the resistance of plants to the larval attack of the species (Costa et al, 2018). Another study showed that adults of D. speciosa when fed with bean leaves, carrot and honey (10%) has higher fecundity and net reproductive rate compared to those adults that fed only of bean leaves (Teodoro et al, 2014). More, Garcia et al (2014) argued that the corn when intercropped with other plants, such as potatoes, soybeans and beans, can affect the spread of adults of D. speciosa in the field, functioning as a natural barrier to this pest, providing population reduction through the insertion corn lines near the starting point of invasion of the pest in the field, acting as the control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the density and type of trichomes expressed by the plant can influence adult feeding behavior. These defense mechanisms can be selected from different cultivars, or incorporated from different species of wild potatoes [82][83][84].…”
Section: Plant Resistancementioning
confidence: 99%